2020
DOI: 10.12659/msm.923921
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Sleep Quality in Individuals Who Self-Isolated for 14 Days During the Coronavirus Disease 2019 (COVID-19) Outbreak in January 2020 in China

Abstract: The presence of COVID-19 has had psychological consequences among health personnel; these include fear, anxiety, and depression. In the current study, we used the Fear of COVID-19 Scale (FCV-19S) to assess the response to fear within health staff in Mexico. This was a cross-sectional survey study in which we administered the FCV-19S to hospital staff. A total of 2,860 participants-1,641 female and 1,218 male personnel from three hospitals-were included in the study. We found a global FCV-19S mean score of 19.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
682
6
69

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 828 publications
(799 citation statements)
references
References 39 publications
(37 reference statements)
42
682
6
69
Order By: Relevance
“…Four studies, all from Chinese centres, examined the frequency of specific mental health-related variables in persons affected by the COVID-19 outbreak Xiao et al, 2020a;Li et al, 2020;Xiao et al, 2020b). Their results are summarized in the Table below ( Table 1).…”
Section: Observational Studies On Mental Health Problems Related To Cmentioning
confidence: 99%
“…Four studies, all from Chinese centres, examined the frequency of specific mental health-related variables in persons affected by the COVID-19 outbreak Xiao et al, 2020a;Li et al, 2020;Xiao et al, 2020b). Their results are summarized in the Table below ( Table 1).…”
Section: Observational Studies On Mental Health Problems Related To Cmentioning
confidence: 99%
“…Particularly for those who live alone and for older people, the current confinement situation may induce or exacerbate loneliness. In fact, a very recent study reporting on citizens' well-being during the COVID-19 outbreak in China showed that those who scored higher on a measure of social participation and a sense of belonging also reported better sleep quality (Xiao, Zhang, Kong, Li, & Yang, 2020b).…”
Section: P Oss Ib Le Neg Ative S Leep-rel Ated Con S Equen Ce S Ofmentioning
confidence: 99%
“…COVID-19 also presents a unique mental health challenge, with several studies detailing the shortand possible long-term effects of quarantine and social isolation on sleep, depression, and anxiety. 8,9,10 These may be exacerbated in those who are already socially isolated or have a chronic illness. 11 Integration of psychiatry, behavioral health, social work, and community partners in the Cleveland Clinic home monitoring program will be key.…”
mentioning
confidence: 99%